(untitled) (Journal of Philosophy Culture and Political Science, 2015)
It’s clear that Maturidi study had appeared before Imam Maturidi or during Maturidi time through the making the decision, conclusion on raised problem. To these problems we can include the value of faith, great sin, and the way of the person in the after world, the freedom of the human desire, the fate and the fate of the people, divine properties, prophetical and the head of the country (caliphate) and other problems. But the main problems were considered and concluded appropriately by Abu Hanifa and his talented followers. However, we should remember that Abu Hanifa and Hanafi scholars’ theological conclusions were adapted to the 8th century requirements. The 10th century requirements had changed, the problems became more complicated, and solutions demanded deep knowledge, all-round searching. Creative, talented thinker Maturidi Imam Hanafi study appeared, and it served the purposes of followed religious movements especially muta- zilites, philosophers, Greek philosophy supporters, Shiites’ points, salaphites.